Edukasi Interaktif Tentang Reproduksi Remaja dalam Menyikapi Bonus Demografi di Madrasah Aliyah DDI Paria - Mutmainnah Mutmainnah; Sukri Nyompa; Nurul Ilmi Rasjusti; Aldhila Gusta Handiarya Yoga; Mar Athul Wazithah (Program Studi Manajemen FEB UNM, 2026)
This study aims to determine the effectiveness of adolescent reproductive education in addressing the demographic bonus at Madrasah Aliyah DDI Paria. Reproductive education plays an important role in shaping adolescents’ awareness of personal health, future planning, and responsibility in facing population-related challenges. Through the distribution of questionnaires to students, the data obtained indicate that the majority of respondents have a good understanding of the material, feel more aware of the importance of maintaining reproductive health, and understand the relationship between reproductive education and the demographic bonus. In addition, participants reported feeling comfortable engaging in discussions, motivated to learn, and prepared to make healthy and responsible decisions. These findings suggest that reproductive education in the madrasah environment is capable of enhancing adolescents’ readiness to face the demographic bonus in a positive and constructive manner. Therefore, this program is considered effective and is recommended to be implemented continuously and sustainably.